Pengaruh Penggunaan Metode Quantum Teaching Terhadap Hasil Belajar pada Kegiatan Praktikum IPA Siswa Kelas V UPTD SDN 3 Parepare - Ila Israwaty; Natriani Syam; Andi Fajar Asti (Seminar Nasional LP2M UNM, 2022)
Abstrak. The purpose of this study was to determine the effect of using the Quantum Teaching method on learning outcomes in science practicum activities for class V UPTD SDN 3 Parepare. The use of the Quantum Teaching method is carried out through 5 stages which include (1) Grow, (2) Experience, (3) Name, (4) Demonstrate, (5) Repeat. The research procedure was carried out in three stages, namely; (1) Giving Pretest, (2) Giving Treatment, (3) Giving Posttest. Obtained from this research through the results of pretest and posttest data analysis, that the use of the Quantum Teaching method affects learning outcomes in science practicum activities for class V UPTD SDN 3 Parepare. This is because in the Quantum Teaching method, students are actively involved in the teaching and learning process both at the beginning of learning to the end of learning so as to create an effective and efficient learning environment. Kata Kunci: Learning Outcomes, Science Learning, Quantum Teaching